2015
DOI: 10.1073/pnas.1415971112
|View full text |Cite
|
Sign up to set email alerts
|

Predator diversity, intraguild predation, and indirect effects drive parasite transmission

Abstract: Humans are altering biodiversity globally and infectious diseases are on the rise; thus, there is interest in understanding how changes to biodiversity affect disease. Here, we explore how predator diversity shapes parasite transmission. In a mesocosm experiment that manipulated predator (larval dragonflies and damselflies) density and diversity, non-intraguild (non-IG) predators that only consume free-living cercariae (parasitic trematodes) reduced metacercarial infections in tadpoles, whereas intraguild (IG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
123
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 50 publications
9
123
1
Order By: Relevance
“…Specifically, the relationship between a protozoan parasite and its herbivore host above ground depends upon the presence and the abundance of soil fungi that influence plant nutritional and defensive traits. Our study also adds to the growing body of literature showing that community composition has profound effects on host-parasite interactions [1][2][3], and that trait-mediated indirect effects can connect below-and aboveground ecosystems [9,10]. As with other studies of AMF, we also found that these effects were dependent on both the abundance of mycorrhizal fungi and the identity of plant species that they colonize [34,35].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Specifically, the relationship between a protozoan parasite and its herbivore host above ground depends upon the presence and the abundance of soil fungi that influence plant nutritional and defensive traits. Our study also adds to the growing body of literature showing that community composition has profound effects on host-parasite interactions [1][2][3], and that trait-mediated indirect effects can connect below-and aboveground ecosystems [9,10]. As with other studies of AMF, we also found that these effects were dependent on both the abundance of mycorrhizal fungi and the identity of plant species that they colonize [34,35].…”
Section: Discussionsupporting
confidence: 79%
“…For example, dilution effects on disease transmission are essentially density-mediated effects in which numerical changes in the relative abundance of competent hosts affect disease transmission [4]. Likewise, trait-mediated indirect effects on host quality, size and behaviour can be equally important [3,[5][6][7][8]45]. Among the factors that influence host-parasite interactions, host diet quality can play a particularly significant role because it can affect host growth rate, immune function and foraging behaviour [7,24,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, during succession or restoration, host species must establish in a community before their parasites can invade (26). More broadly, theoretical models suggest that the effect of biodiversity on disease depends on the traits of hosts, parasites, and additional species (27,28). However, our meta-analysis detected dilution effects robustly across variation in study design, resistance traits of diluting hosts, host range of parasites (human vs. wildlife), and parasite lifecycle and type (macro-vs. microparasite; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nonfocal host species can inhibit disease spread by regulating host populations via competition or predation, interfering with the transmission process, or altering host behavior (6,8). Theoretical models can generally delineate which mechanisms can promote or inhibit disease (27,28), but experimental tests that assess the relative importance of these mechanisms, their generality across disease systems, and their dependence on temporal and spatial scales remain scarce. These open issues represent increasingly important intersections among ecology, conservation science, and epidemiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation